Pulmonary Tuberculosis in the Sebha City, Libya (study in Medical geography)2010-2016 (Journal of Human Sciences, 2018)
Tuberculosis is a deadly disease that spreads among individuals in human populations through infection. Long time ago, societies are making efforts to combat it by using all possible means to defeat it. The prevention from this disease does not mean protecting the individual falling victim to the disease alone, but it is also the protection of society as a whole from its riskiness, which paralyzes its movement towards growth and development, and ends it to destruction and annihilation. This research has tried to monitor the disease throughout the city of Sebha it is an attempt to identify the causes of its spread, relying on the records of health centers in the city, which provided us with important statistics and information. After comparison and analysis, it was found to bear a serious indication of the possibility spreading the disease in this city and the surrounding areas. Therefore, the protection from the disease needs more attention as well asraising the level of awareness of the citizens to be able to protect themselves and avoid becoming a victim of such diseases.